Association of metabolism‐related genes polymorphisms with adenocarcinoma of the oesophagogastric junction: Evidence from 2261 subjects. Issue 11 (18th June 2019) - Tang, Weifeng; Liu, Jun; Zhong, Zhihui; Qiu, Hao; Kang, Mingqiang
Abstract: The etiology of adenocarcinoma of the esophagogastric junction (AEG) remains unclear. It is believed that the increasing of AEG may be correlated with the elevated ratio of obesity and overweight. Thus, metabolism‐related genes and variants may play important roles in the occurrence and progress of AEG. The current investigation involved 720 patients with AEG and 1541 healthy controls. We selected transcription factor 7‐like 2 ( TCF7L2 ) rs7903146 and rs290481, INS rs689 and INSR rs1799817 single‐nucleotide polymorphisms (SNPs), and explored the association of these SNPs with lymph node status and risk of AEG. The polymerase chain reaction was harnessed to identify the genotyping of four polymorphisms. We found that TCF7L2 rs290481 (T > C) and INSR rs1799817 (G > A) polymorphisms were associated with the increased susceptibility of AEG ( P = .007 and 0.004 for TCF7L2 rs290481 in TC vs TT and TC/CC vs TT models, and P = .040 for INSR rs1799817 in GA/AA vs GG model). We also conducted a subgroup analysis by different cancer stage. We identified that TCF7L2 rs290481, INS rs689, and INSR rs1799817 SNPs increased the susceptibility of AEG in different cancer stage subgroups. In addition, we found that rs290481 SNP in TCF7L2 gene increased the risk of lymph node metastasis in drinking patients with AEG. However, the association of INSR rs1799817 SNP with a decreased risk of lymph node metastasis in smoking patients with AEG was found. Our findings highlight that TCF7L2 rs290481, INS rs689, and INSR rs1799817 polymorphisms may increase the risk of AEG. In addition, TCF7L2 rs290481 and INSR rs1799817 SNPs may influence the lymph node metastasis in patients with AEG.